2003
DOI: 10.1177/039463200301600203
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Borrelia Burgdorferi Sensu Lato Genomospecies and of the Human Granulocytic Ehrlichiosis (HGE) Agent in Ixodes Ricinus Ticks Collected in the Area of Monti Lepini, Italy

Abstract: Ticks are obligate hematophagous arthropods that are parasites in every class of vertebrates in most regions of the world. They are also considered to be important vectors for the transmission of human infectious diseases. In the present study we used polymer chain reaction (PCR) amplification analysis to determine the prevalence of Borrelia burgdorferi and Ehrlichia phagocytophila, the agents of, respectively, Lyme borreliosis and human granulocytic ehrlichiosis, among ticks inhabiting the area of Monti Lepin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
(12 reference statements)
0
8
0
Order By: Relevance
“…burgdorferi s.l. is currently considered the most common tick-borne pathogen in the northern hemisphere and it has been frequently detected in ticks and wild animals in Italy [17][18][19][20][21][22]. Several vertebrates are involved in the cycle of this agent, but the role of wild boars is currently not defined [7].…”
Section: Resultsmentioning
confidence: 99%
“…burgdorferi s.l. is currently considered the most common tick-borne pathogen in the northern hemisphere and it has been frequently detected in ticks and wild animals in Italy [17][18][19][20][21][22]. Several vertebrates are involved in the cycle of this agent, but the role of wild boars is currently not defined [7].…”
Section: Resultsmentioning
confidence: 99%
“…Many investigations in Italy have been conducted in mountain and wild habitats (Cacciapuoti et al., 1995; Cinco et al., 1997, 1998; Ciceroni et al., 1998; Mannelli et al., 1999, 2003; Favia et al., 2001; Rizzoli et al., 2002; Santino et al., 2002, 2003; Bertolotti et al., 2006; Mantelli et al., 2006; Piccolin et al., 2006; Pecchioli et al., 2007). However, there is a lack of studies performed in periurban parks.…”
Section: Discussionmentioning
confidence: 99%
“…Mixed infections with two or more Borrelia species are frequent in ticks (Santino et al , 1998; Santino et al , 2003) and have been reported also in human patients (Ruzicā€Sablijic et al , 2005). The present study indicates that human patients with Lyme borreliosis can simultaneously harbor different B. burgdorferi s.l .…”
Section: Discussionmentioning
confidence: 99%